Oxford dictionary of proverbs / edited by Jennifer Speake ; Previously co-edited with J A Simpson - Simpson, John A Previously co-edited
This unique and authoritative dictionary contains over 1,100 of the most widely used proverbs in English, utilizing the latest research from Oxford Dictionaries to source them. This edition has been thoroughly revised and updated, broadening the cultural range of the proverbs selected, and covering sayings of international origins. With a strong emphasis on concisely explaining the meaning of the proverbs described, the dictionary also provides additional examples of usage, and includes a fascinating history for many entries. Arranged in A-Z order and with a useful thematic index, A Dictionary of Proverbs is ideal for browsing and perfectly suited for quick reference. Look up your old favourites, learn punchy new expressions to get your point across, and find the answer to that crossword clue. It is never too late to learn: find proverbs relevant to every aspect of life in this entertaining and informative collection.